Advances in child development and behavior. Volume 2 - Lipsitt, Lewis P.; Spiker, Charles C. (New York : Academic Press, 1965)
Research papers on research frontiers, including learning and behavior in infants, electrophysiological phenomena, attention, perceptual integration, social reinforcement, and physical growth.
Bibliografija iza svakog poglavlja